Anthropological and historical perspectives on India's working classes - Sanchez, Andrew; Strümpell, Christian (Modern Asian studies, 2014)
With reference to original ethnographic and historical research on India, the papers collected in this forum suggest conceptual refinements that might re-centre the study of class in regional scholarship. Through discussions of class politics in industrial, construction and agricultural contexts, the authors interrogate the conceptual oppositions between stably employed fordist labour forces and the ‘working poor’ that have often constrained ethnographic and historical analyses of India's working classes. Inspired by Marxist historiography, this forum engages with the historically contingent emergence of Indian working classes through different types of labour, gender and ethnic struggles, and considers the complex political boundaries that are produced by such processes.
Gesehen am 04.09.2020